Representasi Kesenian Tradisi Lenong Betawi Pada Tayangan Drama Komedi Nglenong Nyok Di Trans TV - Falasifah, Anna; Sugihartono, Ranang Agung (Capture : Jurnal Seni Media Rekam, 2014)
This discussion is intended to know the form of display of comedy drama of Nglenong Nyok, and how this comedy drama represents lenong Betawi traditional art in its display. This study was a descriptive qualitative study using an embedded single strategy. Source of data obtained from informants, documents, books, audio-visual displays, and internet. The sampling technique used was purposive sampling. Data were analyzed using an interactive model. The results showed that Nglenong Nyok is an event with a sitcom format, which looks at the troubleshooting at the end of each episode within 30 minutes and the fourth element which is characteristic of a sitcom that is the fact that the story is presented, the language used, characters, and place. Overall, the comedy drama of Nglenong Nyok as an adaptation display can represent a lenong show into the display, although the production process has undergone development in some elements. Still keepholding on guidelines (grip, Java) of the showlenong Betawi is evidence that the comedy drama of Nglenong Nyok is able to represent the lenong show in the middle of the television business that requires the program makers to be more concerned with profit than the quality. Keywords: representation, Lenong, Betawi, Nglenong Nyok, and Trans-TV